Nivel de conocimiento y prácticas de las/os enfermeras/os sobre medidas de bioseguridad en áreas críticas del Hospital Regional de Loreto, enero – abril 2013 - Farfán Pinedo, Carlos Bennynllers (2013)
The present investigation was to determine the level of knowledge and practices of the / o Nurses / os on biosecurity measures in critical areas Loreto Regional Hospital from January to April of 2013 . The research was descriptive correlational , quantitative , non-experimental , prospective, cross-sectional , population consisted of nurses and nurses working in critical areas ( emergency , burn unit , hemodialysis and intensive care unit pediatric , surgery, and medicine, and neonatology ) Loreto Regional Hospital , with a total of 43 of which 39 represent the sample, the type of sample used was stratified probability sampling . The method for data collection was a survey and observational record . The survey consisted of 20 items that measured the level of knowledge about biosecurity measures , and observational guide consisted of 39 items that measured practices / the nurses / os on biosecurity measures in critical areas Loreto Regional Hospital . The data processing was performed according to the scale of measurement used by computer through the Microsoft Excel program , and to establish the relationship between the variables under study using the statistical package SPSS Statistics , applying the Student t test . The results were that of the 39 nurses / o 56% ( 22) has a good knowledge level , 41% ( 16 ) has a regular knowledge level and only 2.6 % ( 1) has a poor level of knowledge , also found that of the 39 nurses / o 74.4 % (29 ) makes a proper practical biosecurity measures and only 25.6 % (10 ) makes an appropriate practice of biosecurity measures. Highlighting inadequate biosecurity practices that does not close the pipe with disposable towel 56.41 % (22 ) , does not change immediately when mandilón visible contamination with body fluids or when the intervention is completed 33.33 % (13 ) , not discarded needles only 69.23 % (27 ) , put the needle protective cap before removing 61.54 % (24 ) , is not stored properly sterile 41.03 % ( 16), and highlighting in appropriate biosecurity practices that they wash their hands after each procedure 77 % (30 ) wash hands before each procedure 92 % ( 36 ) , using N -95 mask in the care of patients with TB , H1N1 , etc. . 97 % ( 38 ) , and staff work accidents reported 97 % ( 38 ) , and was obtained through the student 's t test there is no significant relationship between the variables Level of Knowledge and Practices of the / o nurses / os on biosecurity measures in critical areas Loreto Regional Hospital with correlation coefficient r of 0.226 concluding that the vast majority of staff nurse working in critical areas has a high knowledge level and practice these protocols biosecurity but having some deficiencies which need improvement suggested by training nurses led by quality area all hospital workers